Patient perspectives on biological treatments for inflammatory arthritis: A multi-center study in Korea - In Ah Choi,; Ji Hyoun Kim,; Sung Hae Chang,; Ran Song,; You-Jung Ha,; Hye Won Kim,; Jeong Seok Lee,; Byoongyong Choi,; Yoon-Jeong Oh,; Ki Won Moon, (Archives of Rheumatology, 2021)
Objectives: The aim of this study was to evaluate the patient’s perception of the use of biological disease-modifying anti-rheumatic drugs (bDMARDs) and provide a basis for physicians to understand the patient’s perspective. Patients and methods: Between December 2018 and June 2019, a total of 307 patients (162 males, 145 females; mean age: 48 years; range, 18 to 81 years) were included in this investigator-initiated, multi-center, observational, and cross-sectional study in six rheumatology centers. We asked patients using bDMARDs to treat rheumatoid arthritis (RA) or ankylosing spondylitis (AS) to complete a questionnaire regarding major considerations and satisfaction with bDMARDs, preferred administration route, knowledge about bDMARDs, experiences of adverse events, non-adherence, and expectations of their healthcare provider. The satisfaction of physician and clinical information on the patient's disease and treatment were also collected. Results: Of the patients, 139 had RA and 168 had AS. Median disease duration was six years in RA and five years in AS. A total of 80.1% of the patients and 77.1% of the physicians indicated being satisfied or very satisfied with the therapeutic effect of the current bDMARD. Most patients were open to intravenous or subcutaneous injection, with the most preferred route of administration being subcutaneous (41.3%), followed by intravenous (32.0%), and oral (26.7%). The patients considered therapeutic effect to be more important than cost or convenience while choosing a bDMARD (69.3%), and most were willing to be educated about therapeutic effects (46.1%). Only 35.2% of the patients reported well and/or very well knowledge about the therapeutic effects, side effects, and administration methods of their current bDMARD, and 86.6% cited their physician as the primary source of information about biological treatment. Conclusion: Patients value therapeutic effect more than cost or convenience while selecting a bDMARD, and consider their physicians to be the primary information source. Therefore, it is important for physicians to provide appropriate education and encourage patients to cooperate actively with treatment.